Analysis of Scale Distance Correlation to Soil Vibration in Coal Blasting Operations - Julianti, Sri Rezeki; Djayus, Djayus; Lepong, Piter (GEOSAINS KUTAI BASIN, 2021)
The optimum vibrations generated from the delay, distance, and explosive settings on the destruction of the ground cover or OB can accumulate the effect of the damage. Research was purposed to view the process of coal blasting and the impact of distance and explosives the detonation process. The data used in the research is a secondary force of distance, explosives, drilling patterm (7 m burden and 8 m distance ) and blasting pattern (Staggered patten/Zig-zag).Data are prepared using Microsoft Excel by inserting distance and explosives materials and for PPV value. PPV value is compared with the distance value (scaled distance). The result of research shows the process of blasting using a zig-zag system with distance between 7m and spacing 8m, depth of 3m - 14m. Explosived material content (ANFO) with averaged 101.74. The impact of the distance and the explosives materials from PPV calculations is not very significantly indicated by the PPV value of 3,62mm/s.